Penggunaan Media Lidi Untuk Meningkatkan Keterampilan Siswa Pada Penjumlahan Bilangan Bulat di Kelas IV MI Hidayatus Syar’iyah Wolo Semester 1 Tahun Pelajaran 2018/2019 - Abdul Rois (ILUMINASI: Journal of Research in Education, 2023)
Using Stick Media to Improve Students' Skills in Adding Whole Numbers in Class IV MI HIDAYATUS SYAR'IYAH WOLO SEMESTER 1 ACADEMIC YEAR 2018/2019.One of the problems relating to the management of the teaching and learning process for mathematics subjects in SD/MI is the lack of knowledge for SD/MI teachers, as well as limited funds and facilities on how to create and use media/visual aids in mathematics learning. On the other hand, the importance of media/visual aids in mathematics learning has been recognized by all levels of education managers and educational experts.This research aims to overcome the problem of learning the addition of whole numbers in class IV MI HIDAYATUS SYAR'IYAH WOLO SEMESTER 1 ACADEMIC YEAR 2018/2019 using stick media. The model applied in this research uses the following steps: First, initial activities include: (a) Explanation of learning objectives, (b) Providing learning motivation, (c) Apperception; Second, the core activities, include: (a) Forming groups, (b) Providing stick media, (c) Brief explanation of how to use the tools, (d) Performance of work, (e) Playing speed fights. Third, Final Activities, include: (a) Discussion of results, (b) Checking skills through question and answer, (c) Evaluation, and (d) Providing follow-up in the form of homework. The learning objective in this research is that using stick media can improve students' skills in adding whole numbers.The approach used in this research is a qualitative approach with the type of classroom action research. The subjects of this research were 20 class IV students of MI HIDAYATUS SYAR'IYAH WOLO SEMESTER 1 OF THE 2018/2019 ACADEMIC YEAR. Data collection techniques regarding students' skills in using media for adding whole numbers are carried out through oral tests at the beginning of the lesson, observation, process evaluation when students demonstrate the media and written evaluation at the end of the lesson.We carried out this research through three stages of action, namely: using stick media in pairs, using colored stick media in pairs and using colored stick media individually. The results of this research show the following: First, the results of the process evaluation (during the implementation of learning) showed that students were very active at 15%, second, at 55%, and third, at 98.3%. Correct tool placement and correct use were 20%, 60%, and 90%. Use of the right tools and correct results was 20%, 50% and 91.5%. The results of the written evaluation of 10 questions via the test sheet, the average mastery of the material was 43.5%, 68.5% and 81.5%. Overall, the implementation of learning using stick media, starting from actions I, II, and III, shows an increase in both skills and understanding of research subjects regarding adding whole numbers.